Japan's prisoners of conscience : protest and law during the Iraq war - Repeta, Lawrence, 1951- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book is a narrative account of the criminal prosecution of three peaceful protesters in Japan during the Iraq War, telling the inside story of their arrests and trial and examines the larger issues raised by the police crackdown on these anti-war protesters. Based on interviews with defendants, lawyers and eyewitnesses, and other Japanese language sources, the book carries rich descriptions of the individuals at the heart of the story, including the charismatic leader of the "Tachikawa Tent Village" who has been protesting since U.S. military forces were stationed in her hometown in the early post-war era. Authored by an attorney who has researched and written on Japanese legal issues for more than three decades and was the plaintiff in a suit that made constitutional history by opening Japan's courts to free reporting, this book offers expert insights into Japan's evolution as a democratic society. Illustrating the sharp political conflict that has deeply affected Japan's defence policy for decades, this book will be of huge interest to scholars and students of Comparative Law, Peace Studies, Japanese Society and Modern Asian History"--
OCLC-licensed vendor bibliographic record.
Keywords: Prisoners -- Japan; Iraq War, 2003-2011 -- Moral and ethical aspects -- Japan; Protest movements -- Japan; LAW / General; SOCIAL SCIENCE / Sociology / General